1973
DOI: 10.1002/j.2333-8504.1973.tb00450.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cognitive Style in Academic Performance and in Teacher‐student Relations12

Abstract: The cognitive characteristics involved in a relatively field-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0
19

Year Published

1973
1973
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 53 publications
3
120
0
19
Order By: Relevance
“…In the domain of cross-cultural psychology, two cultural typologies may be theoretically associated with the learning abilities of Kolb's model. One typology focuses on culturally different self-construals of interdependent-self and independentself presented and is discussed by Markus and Kitayama (1991), while the other is Witkin's (1976) cognitive style of field-dependent and field-independent.…”
Section: Cross-cultural Psychologymentioning
confidence: 99%
See 3 more Smart Citations
“…In the domain of cross-cultural psychology, two cultural typologies may be theoretically associated with the learning abilities of Kolb's model. One typology focuses on culturally different self-construals of interdependent-self and independentself presented and is discussed by Markus and Kitayama (1991), while the other is Witkin's (1976) cognitive style of field-dependent and field-independent.…”
Section: Cross-cultural Psychologymentioning
confidence: 99%
“…Field-dependent and field-independent Witkin's (1976Witkin's ( , 1979 cognitive styles of field-dependent and field-independent have influence upon cross-cultural studies of psychological development across cultures (Goodenough, 1986). Witkin and his colleagues (1954) found that people's perception of the upright is consistently stable and represents part of their fundamental psychological makeup.…”
Section: Propositionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Cognitive Control Theory, [7] field dependence/independence is not only a cognitive style but also a cognitive control.…”
Section: G Formation Of Fd/imentioning
confidence: 99%